Trial of atorvastatin on serum interleukin-6, total antioxidant capacity, C-reactive protein, and alpha-1 antitrypsin in patients with chronic obstructive pulmonary disease - Anahita Arian; Sayyed Gholamreza Mortazavi Moghadam; Tooba Kazemi; Mahmood Zardast; Asghar Zarban (Wolters Kluwer Medknow Publications, 2018)
Objective: The present study was designed to investigate the effects of atorvastatin on serum high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), total antioxidant capacity (TAC), and alpha-1 antitrypsin (AAT) in patients with chronic obstructive pulmonary disease (COPD). Methods: A clinical trial study conducted on 42 cases of COPD (Vali-Asr Hospital, Birjand, East of Iran, years 2014-16). Patients were randomly assigned to 21 controls and 21 cases who treated with atorvastatin (40 mg/day for 6 months). Inhaled corticosteroid and long-acting β-agonist were administrated in both groups. The trial was registered at the Iranian Registry of Clinical Trials (registration number: IRCT2016042527594N1). TAC was measured by ferric reducing/antioxidant power assay. An enzyme-linked immunosorbent assay was used to determine IL-6, AAT, and hs-CRP. Spearman's rho test and Wilcoxon, Mann-Whitney, paired, and independent t-tests were used for data analysis in SPSS 23. P < 0.05 was considered significant. Findings: A number of patients completed the study were 16 in atorvastatin and 18 in control group. Mean increments (μmol/L) of TAC (mean ± standard deviation [SD]) were 12.81 ± 605.25 (P = 0.68) in atorvastatin and 160.26 ± 280.54 (P = 0.14) in control group. Mean decrements of IL-6, CRP, and AAT (mean ± SD) were 1.41 ± 5.51 (P = 0.71), 0.98 ± 5.68 (P = 0.72), and 10.94 ± 46.83 (P = 0.21) in atorvastatin and 0.91 ± 11.70 (P = 0.75), 3.23 ± 7.00 (P = 0.19), and 18.77 ± 55.90 (P = 0.21) in control group. Conclusion: Atorvastatin did not succeed in maintaining TAC and CRP reduction. However, less reduction in AAT and more reduction in IL-6 in the atorvastatin group would be likely a beneficial effect in COPD.